2016
DOI: 10.1186/s12885-016-2737-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the efficacies of gonadotropin-releasing hormone (GnRH) agonist and GnRH antagonist in neoadjuvant androgen deprivation therapy combined with transperineal prostate brachytherapy for localized prostate cancer

Abstract: BackgroundNeoadjuvant androgen deprivation therapy (ADT) has been suggested to confer several clinical benefits in patients with prostate cancer (PCa) undergoing transperineal prostate brachytherapy (TPPB). Unlike gonadotropin-releasing hormone (GnRH) receptor agonists, a GnRH antagonist such as degarelix can achieve castrate levels of testosterone without testosterone flare. However, normalization of serum testosterone levels following completion of neoadjuvant ADT in either form of treatment has never been c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Additionally, Van Coppenolle et al (8) demonstrated that T levels are higher in controls compared with animals treated with sulpiride, which is not congruent with the aforementioned results. Previous studies have indicated that an increase in PRL inhibits gonadotrop-releasing hormone (GnRH) release from the hypothalamus and reduces LH release via a negative feedback regulatory mechanism (54,55). The structure and function of the prostate are influenced by the hypothalamus-pituitary-gonadal axis (56), while tissue growth and hormone secretion are primarily affected by T regulation (57).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Van Coppenolle et al (8) demonstrated that T levels are higher in controls compared with animals treated with sulpiride, which is not congruent with the aforementioned results. Previous studies have indicated that an increase in PRL inhibits gonadotrop-releasing hormone (GnRH) release from the hypothalamus and reduces LH release via a negative feedback regulatory mechanism (54,55). The structure and function of the prostate are influenced by the hypothalamus-pituitary-gonadal axis (56), while tissue growth and hormone secretion are primarily affected by T regulation (57).…”
Section: Discussionmentioning
confidence: 99%
“…For all patients, TPPB was administered using an ultrasound-guided technique with either the Mick applicator or an intraoperatively built custom-linked seed technique. 11 The implant was planned to deliver a dose of at least 144 Gy to the clinical target volume, which included the prostatic gland and treatment margin. All participating patients completed TPPB.…”
Section: Treatment Protocolmentioning
confidence: 99%
“…This class of drug binds to the unique region in the N-terminal domain of both full-length and truncated constitutively active splice variant of AR [40]. c. ADT that effectively reduces the serum testosterone levels has been a core tool for treating metastatic and advanced prostate cancer [48]. However, neoadjuvant ADT has been suggested to have several advantages in prostate cancer patients undergoing transperineal prostate brachytherapy.…”
Section: Androgen Deprivation Therapy (Adt)mentioning
confidence: 99%
“…The agents that are mainly used as adjuvant ADT include estrogens, antiandrogen monotherapy, and combined androgen blockade (CAB) using antiandrogen plus a gonadotropin-releasing hormone receptor (GnRH) agonist. It has been reported that in comparison to GnRH agonist, degarelix, a GnRH receptor antagonist, is more efficient in achieving castration levels of testosterone and PSA, without risk of testosterone flare [48,49].…”
Section: Androgen Deprivation Therapy (Adt)mentioning
confidence: 99%